Challenges Facing Early Career Academic Cardiologists - Tong, Carl W. (J Am Coll Cardiol, 2014)
Early-career academic cardiologists currently face unprecedented challenges that threaten a highly valued career path. A team consisting of early career professionals and senior leadership members of American College of Cardiology (ACC) completed this white paper to inform the cardiovascular medicine profession regarding the plight of early career cardiologists and to suggest possible solutions. This paper includes: (1) definition of categories of early career academic cardiologists, (2) general challenges to all categories and specific challenges to each category, (3) obstacles as identified by a survey of current early career members of the ACC, (4) major reasons for the failure of physician-scientists to receive funding from National Institute of Health/National Heart Lung and Blood Institute (NIH/NHLBI) career development grants, (5) potential solutions, and (6) a call to action with specific recommendations.